Sobre la alteridad en la frontera de Granada : (una aproximación al análisis de la guerra y la paz, siglos XIII-XV) - García Fernandez, Manuel (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
Studies on the diverse forms of alterity on the Border front of Granada during the historical period of its genesis, evolution and definition (13th-15th centuries), are not unlike other border-related issues that were amply commented on in the medieval historiography of Andalusia. The scarcity and difficulty of known document sources undoubtedly restricts our understanding; or rather confines it to perspectives imposed by the dominant Christians. In Andalusia, the image of the neighbouring realm – basically that of Muslim Granada – is shaped by negative / positive features arising from relations evolving around daily survival, which, in turn, were based on war and peace as a way of life, and on the institutions that guaranteed the peaceful coexistence between two cultures, which were nevertheless antagonistic. The Crown, the king’s officials and the Castilian noblemen did not always understand or accept the forms of alterity of the Southern inhabitants as correct. Thus, peripheral attitudes and mutual relations emerged that often diverged from the official directives. El enemigo en el espejo (The enemy in the mirror).